2011
DOI: 10.4049/jimmunol.1003246
|View full text |Cite
|
Sign up to set email alerts
|

A Serine Proteinase Homologue, SPH-3, Plays a Central Role in Insect Immunity

Abstract: Numerous vertebrate and invertebrate genes encode serine proteinase homologues (SPHs) similar to members of the serine proteinase family, but lacking one or more residues of the catalytic triad. These SPH proteins are thought to play a role in immunity, but their precise functions are poorly understood. In this study, we show that SPH-3 (an insect non-clip domain–containing SPH) is of central importance in the immune response of a model lepidopteran, Manduca sexta. We examine M. sexta infection with a virulent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…Intriguingly, recently we succeeded in showing that all of the steps in the proPO-cascade in Tenebrio molitor are shared with the proteinase cascade that leads to the activation of the Toll pathway for the production of antimicrobial peptides [10]. This shared cascade has been confirmed in several other insects [11], [12]. In the present study, we found that caspases are very important for the rapid degradation of proPO, which prevents oxidation in places where it is not appropriate.…”
Section: Introductionsupporting
confidence: 77%
“…Intriguingly, recently we succeeded in showing that all of the steps in the proPO-cascade in Tenebrio molitor are shared with the proteinase cascade that leads to the activation of the Toll pathway for the production of antimicrobial peptides [10]. This shared cascade has been confirmed in several other insects [11], [12]. In the present study, we found that caspases are very important for the rapid degradation of proPO, which prevents oxidation in places where it is not appropriate.…”
Section: Introductionsupporting
confidence: 77%
“…Both genes were induced at 11 h postexposure, but the gene encoding tyrosine-protein phosphatase non-receptor type 23-like, which is involved in positive regulation of the Toll pathway, was repressed at 12 h postexposure. The Toll pathway is generally triggered by a cascade of serine proteases upon immunological challenge and PGRP-based recognition (Lemaitre & Hoffmann, 2007;Felfoldi et al, 2011). In insects, serine proteases are known to perform functions of digestion, embryonic development and defence responses towards both microbial and parasite invaders (Rawlings & Barrett, 1993;Kanost, 1999;Krem & Di Cera, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigations based on RNAi studies of genes encoding defense effector proteins and genes encoding the PRPs suggest that the PRP signaling pathway has a much greater impact on an insect’s survival after infection than does the effector gene pathway [58,59]. Thus, it is reasonable to assume that the ability of S .…”
Section: Discussionmentioning
confidence: 99%